Do bank bailouts have an impact on the underwriting business? - Carbó-Valverde, Santiago; Cuadros-Solas, Pedro J.; Rodríguez-Fernández, Francisco (Journal of Financial Stability, 2020)
We explore the effects of bank bailouts on competition in the underwriting business. We exploit a sample of underwriters active in the European corporate bond markets from 2006 to 2013 and find that reputable underwriters suffer market share losses (of 12.43 %) after being bailed out. However, the market share of non-reputable underwriters is found to increase after a bail out. An exploration of the firm–bank underwriting matching reveals that the probability of being chosen as underwriter in a given deal decreases for reputable bailed-out banks, while it increases for non-reputable bailed-out banks. These results provide evidence of the effects of bailouts on underwriting competition. The economic impact depends on the ex-ante reputational capital of the bailed-out bank.